2008
DOI: 10.1002/lt.21575
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of follow-up of aortohepatic conduits in liver transplantation

Abstract: Arterial problems remain a formidable challenge in liver transplantation. In many situations, an aortohepatic conduit can provide a solution. No long-term results (over 5 years) have been reported. This study was designed to assess the impact of aortohepatic conduits on graft survival after liver transplantation and the safety of aortohepatic conduits and to establish the long-term results (up to 20 years) of aortohepatic conduits. Data from 2346 adult liver transplants were prospectively collected into the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
4
25
0
Order By: Relevance
“…6,7 In comparison with other techniques, [8][9][10] such as the extra-anatomic aortohepatic conduit technique, results were better at our center, although not statistically different. This study is important because the Namazi Transplant Center in Shiraz (Iran) was the most crowded transplant center of the world during our study period, and we can now present our results to other centers.…”
Section: Discussionmentioning
confidence: 53%
“…6,7 In comparison with other techniques, [8][9][10] such as the extra-anatomic aortohepatic conduit technique, results were better at our center, although not statistically different. This study is important because the Namazi Transplant Center in Shiraz (Iran) was the most crowded transplant center of the world during our study period, and we can now present our results to other centers.…”
Section: Discussionmentioning
confidence: 53%
“…Nikitin et al reported similar long-term survival for LT utilizing arterial conduits as compared to LT employing standard arterial reconstructions [1]. Although LT using arterial conduits can be performed safely in experienced hands, arterial conduits carry a potential for increased posttransplant complications and also higher rates of graft loss.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial conduits are necessary in nearly 5% of all liver transplants [1, 2]. A segment of donor iliac artery usually is utilized as the arterial conduit, bridging recipient's infrarenal aorta to hepatic artery of the liver allograft (HAA) [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…1 In the majority of cases, donor iliac or carotid arteries are used as arterial conduits, and they are anastomosed to the infrarenal aorta as a source of inflow. 2 The original technique involves retropancreatic tunnelization anterior to the inferior vena cava (the short route) or to the left of the superior mesenteric artery (the long route). 3 Tzakis et al 4 later described the anterior route, in which the graft passes anterior to the pancreas but posterior to the stomach and colon; this offers the advantage of avoiding retroperitoneal dissection and retropancreatic varices.…”
Section: To the Editorsmentioning
confidence: 99%